PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER (NHT) DIIRINGI DENGAN HANDOUT TERHADAP HASIL BELAJAR BIOLOGI SISWA KELAS VIII DI SMPN 2 BATANG ANAI - Agusiah, Agusiah; Risdawati, Renny; Yasmi, Fifi (STKIP PGRI Sumbar, 2014)
ABSTRACÂ This researchis refering to the result of the biology student in learning process at SMPN 2 Batang Anai. All this because of some factors, such as the students are not active in learning process. And prefer to wait and listen to the teachers explaination. They do not want to ask the question about the material that they dont really understand. One of the best way to increase the result of learnig process is cooperative learning model type numbered head together (NHT) following by handout. The aim of this research is to know about the result of learning process in using kooperatif learning type numbered head together (NHT) following by handout to the students in VIII class at SMPN 2 Batang Anai. This reasearch called experiment reaserch by using randomized control group posttest only desingn. The population in this research is VIII class at SMPN 2 Batang Anai in 2013/2014 that consits of 8 classes. Sample is taken by using purposive sampling technique,so that, it found 2 classes sampling with random. The result, there are VIII6 class as a Â experimental class and VIII7 class as a control class. The data is analyted by using t- tes with corelation by real step 0,05. The result of data analysis is found t hitung 1,93 where as t tabel 1,67. It Â means the cooperative learning model type numbered head together (NHT) following by handout can improve the result of students biology in learning process is better than before in VIII class at SMPN 2 Batang Anai.